Antifibrotic Effects of Tetrahedral Framework Nucleic Acids by Inhibiting Macrophage Polarization and Macrophage–Myofibroblast Transition in Bladder Remodeling. Issue 11 (16th January 2023) - Wang, Wei; Xiao, Dexuan; Lin, Lede; Gao, Xiaoshuai; Peng, Liao; Chen, Jiawei; Xiao, Kaiwen; Zhu, Shiyu; Chen, Jixiang; Zhang, Fuxun; Xiong, Yang; Chen, Huiling; et al.
Abstract: Bladder outlet obstruction (BOO) is a prevalent condition arising from urethral stricture, posterior urethral valves, and benign prostatic hyperplasia. Long‐term obstruction can lead to bladder remodeling, which is characterized by inflammatory cell infiltration, detrusor hypertrophy, and fibrosis. Until now, there are no efficacious therapeutic options for BOO‐induced remodeling. Tetrahedral framework nucleic acids (tFNAs) are a type of novel 3D DNA nanomaterials that possess excellent antifibrotic effects. Here, to determine the treatment effects of tFNAs on BOO‐induced remodeling is aimed. Four single‐strand DNAs are self‐assembled to form tetrahedral framework DNA nanostructures, and the antifibrotic effects of tFNAs are investigated in an in vivo BOO animal model and an in vitro transforming growth factor beta1 (TGF‐ β 1)‐induced fibrosis model. The results demonstrated that tFNAs could ameliorate BOO‐induced bladder fibrosis and dysfunction by inhibiting M2 macrophage polarization and the macrophage–myofibroblast transition (MMT) process. Furthermore, tFNAs regulate M2 polarization and the MMT process by deactivating the signal transducer and activator of transcription (Stat) and TGF‐ β 1/small mothers against decapentaplegic (Smad) pathways, respectively. This is the first study to reveal that tFNAs might be a promising nanomaterial for the treatment of BOO‐induced remodeling. Abstract : Tetrahedral framework nucleic acids (tFNAs) are a type of novel 3D DNA nanomaterials that are assembled by four specially designed single‐stranded DNA molecules based on Watson–Crick base pairing. tFNAs can regulate M2 polarization and the macrophage–myofibroblast transition, thus efficiently ameliorating bladder fibrosis and dysfunction.